Language Policies and Ideologies for Socialization and Identity-Building in U.S. Schools: The Case of Newcomer and Refugee Students in Arizona and New York - S. Garnett Russell; Camille Fabo; Victoria Jones; Arnela Colic (Social Sciences)
Although multilingualism is a major issue in educational policies, especially in states hosting a high number of newcomer immigrant students, there is limited research exploring the experiences of a multilingual group of newcomer students and how they use language in schools. This article draws on 112 interviews with students from an immigrant background across four high schools in Arizona and New York. We illuminate the role of language in shaping identity and inclusion. Through conceptualizing power and language ideology, we find that language ideologies and practices shape the perception of students’ social interactions in school settings. Our findings also indicate that teachers’ practices and school policies surrounding language(s) have the potential to affect how students view language in relation to their own identity and via social interactions. We contribute to an understanding of how language policies and ideologies shape the experiences and power dynamics of diverse, multilingual, immigrant-origin students.